Analysis of midwives' knowledge regarding the use of acupressure on pregnant women at Ingin Jaya Community Health Center, Aceh Besar - Idiana, Adri; Noviyanti, Noviyanti; Dewi, Ratna; Juliastuti, Juliastuti; Faisal, T Iskandar (Science Midwifery, 2024)
This study aims to analyze the level of midwives' knowledge regarding the use of acupressure on pregnant women at the Ingin Jaya Community Health Center, Aceh Besar. The research method employed in this study involved surveying and analyzing data from a number of midwives stationed at the Ingin Jaya Community Health Center. The survey was conducted using a specially designed questionnaire to measure midwives' knowledge about various aspects of acupressure including how to perform it, its usage, benefits, contraindications, and knowledge of acupressure points on pregnant women at the Ingin Jaya Community Health Center, Aceh Besar. The study found that midwives' knowledge of using acupressure on pregnant women in Indonesia is still limited. The majority of midwives have insufficient understanding of various aspects of acupressure such as its techniques, benefits, and relevant acupressure points. This limited understanding may affect the quality of prenatal care they provide. After the intervention, the majority of respondents achieved a post-test percentage above 75%, with some even reaching 90%. This indicates the significant effectiveness of complementary acupressure therapy in improving the respondents' conditions after the intervention. There was variation in the percentage of improvement between pre-test and post-test scores among the respondents. However, overall, it is evident that most respondents experienced consistent improvements in post-test percentages.